ERRATUM: ERRATUM - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2024)
Erratum to: Ayusma AN, Widiastuti A, Arwiyanto T. 2024. Potency of Eucalyptus Oil and Citronella Oil in Suppressing Virulence Factors of Xanthomonas oryzae pv. oryzae. Jurnal Fitopatologi Indonesia. 20(4):195–203. DOI: https://doi.org/10.14692/jfi.20.4.195–203. In this published version of the article, there are no Acknowledgements. A changes have been made in the latest version, adding the Acknowledgements “The authors would like to express their sincere gratitude to the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) in the Philippines for providing the financial support that made this research possible. This study was conducted with funding from SEARCA, whose commitment to advancing agricultural research in Southeast Asia has been invaluable”. The correction has been made on the website and in the PDF version of the article.